Measuring Project Management Performance: Case of Construction Industry. Issue 4 (2nd October 2017) - Demirkesen, Sevilay; Ozorhon, Beliz
Abstract: This study develops construction-specific determinants and indicators of project management performance based on the 14 knowledge areas of the project management body of knowledge guide. Interrelations among the knowledge areas and influence of these factors on performance are investigated. Data collected from 121 construction projects are analyzed using structural equation modeling. Research findings suggest that project integration, communications, safety, risk, human resources, financial, and cost management have a direct impact, whereas scope and time management have an indirect effect on performance. The findings reported in this study are expected to help construction project managers devise and implement strategies and develop actions to improve project success. An engineering manager can use the framework developed in this research to define the underlying factors of efficient project management practices.